ISLAMIC STUDIES: THE APPEARANCE AND HISTORY OF THE DEVELOPMENT OF ORIENTALISM - AHMAD SODIKIN; WAHYU LENGGONO (UIN Kiai Ageng Muhammad Besari Ponorogo, 2023)
This article discusses the study of orientalism and its history of development. This research is a qualitative research by using the method of library or library research that the author describes the study of orientalism and history of defelopment through a word (descriptive) based on information or data obtained from books and journals. In addition, this paper is intended to know correctly and deeply about the study of orientalism and its development, so that readers have good knowledge of orientalism. Based on the study conducted by the authors can be argued that orientalisme is an understanding whose activities are conducting an assessment of eastern, especially in the field of religion, science, culture and others. Orientalism emerged in the part of the European world spearheaded by church orientalists who came to Andalusia to study the eastern. Orientalism shows a remarkable development marked by numerous works, school institutions, universities, magazines, and congresses it does for the sake of orientalism.